Characterization of a Human Induced Pluripotent Stem Cell–Derived Cardiomyocyte Model for the Study of Variant Pathogenicity: Validation of a KCNJ2 Mutation. (October 2017) - Gélinas, Roselle; El Khoury, Nabil; Chaix, Marie-A.; Beauchamp, Claudine; Alikashani, Azadeh; Ethier, Nathalie; Boucher, Gabrielle; Villeneuve, Louis; Robb, Laura; Latour, Frédéric; Mondesert, Blandine; Rivard, Lena; et al.
Abstract : Background—: Long-QT syndrome is a potentially fatal condition for which 30% of patients are without a genetically confirmed diagnosis. Rapid identification of causal mutations is thus a priority to avoid at-risk situations that can lead to fatal cardiac events. Massively parallel sequencing technologies are useful for the identification of sequence variants; however, electrophysiological testing of newly identified variants is crucial to demonstrate causality. Long-QT syndrome could, therefore, benefit from having a standardized platform for functional characterization of candidate variants in the physiological context of human cardiomyocytes. Methods and Results—: Using a variant in Kir2.1 (Gly52Val) revealed by whole-exome sequencing in a patient presenting with symptoms of long-QT syndrome as a proof of principle, we demonstrated that commercially available human induced pluripotent stem cell–derived cardiomyocytes are a powerful model for screening variants involved in genetic cardiac diseases. Immunohistochemistry experiments and whole-cell current recordings in human embryonic kidney cells expressing the wild-type or the mutant Kir2.1 demonstrated that Kir2.1-52V alters channel cellular trafficking and fails to form a functional channel. Using human induced pluripotent stem cell–derived cardiomyocytes, we not only confirmed these results but also further demonstrated that Kir2.1-52V is associated with a dramatic prolongation of action potential duration with evidence of arrhythmic activity, parameters which could not have been studied using human embryonic kidney cells. Conclusions—: Our study confirms the pathogenicity of Kir2.1-52V in 1 patient with long-QT syndrome and also supports the use of isogenic human induced pluripotent stem cell–derived cardiomyocytes as a physiologically relevant model for the screening of variants of unknown function. Abstract : Supplemental Digital Content is available in the text.